Tandem α‐Alkylation/Asymmetric Transfer Hydrogenation of Acetophenones with Primary Alcohols. Issue 30 (15th September 2014) - Kovalenko, Oleksandr O.; Lundberg, Helena; Hübner, Dennis; Adolfsson, Hans
Abstract: A tandem α‐alkylation/asymmetric transfer hydrogenation of acetophenones with primary alcohols, mediated by a single ruthenium catalyst, is described. Under optimized reaction conditions and with use of [Ru( p ‐cymene)Cl2 ]2 in combination with an amino acid hydroxyamide ligand, the chiral secondary alcohol products were isolated in moderate yields and in moderate to good enantiomeric excess (up to 89 % ee ). Abstract : One catalyst – one pot – two reactions. Acetophenones are initially alkylated with primary alcohols by the borrowing hydrogen methodology. The alkylation products are directly converted to enantiomerically enriched secondary alcohols.